A review on physicochemical and thermorheological properties of sago starch - Mohamed Saeed, Mohamed Abd Elgadir; Bakar, Jamilah; Abbas, Kassim Ali; Abdul Rahman, Russly; Karim, Roselina (Science Publications, 2008)
This study was a part of a research project aiming to investigate the texture characteristics of protein - starch interaction in fish based product keropok lekor. Accordingly, the current review study focused on some physicochemical (molecular weight, viscosity, chemical composition and swelling power) and thermorheological (gelatinization, retrogradation and viscoelsticity) characteristics of sago starch alone and in mixtures with other ingredients such as sucrose, salts and hydroclloids. The inferred outcome of this extensive survey revealed that the gelatinisation temperature for sago-water mixture ranged from 69.4-70.1°C which was low compared to sweet potato, tania and yam starches. The role of using hydrocolloids in starch-based foods was to control the rheological properties as well as modifying the texture of the products, enhaning or modifying the gelatinization and retrogradation behaviour and improving water-holding capacity of the system. In the presence of sucrose or sodium chloride, the gelatinisation temperatures of sago starch shifted to higher temperatures and its enthalpy decreased. The addition of salts caused an elevation or depression of gelatinization temperature and gelatinization enthalpy, depending on their types and concentrations used. However, sodium chloride appeared to exhibit a maximum inhibitory effect on starch gelatinisation at a concentration of 6-9%.